KOMPETENSI PENDAMPINGAN PEMANDU WISATA LOKAL SEBAGAI DEVELOPERS OF PEOPLE - Bambang Supriadi (Universitas Merdeka Malang, 2016)
Opportunity tourism growth in real terms to increasing employment opportunities and improving the competitiveness of the nation if it is followed by improving the quality of human resources, in view of improving the quality of tourism human resources will play a role as a contributor in improving the quality of tourist satisfaction, Therefore the purpose of this research focuses on the analysis of the description quality mentoring group for a local tour guide services is grown (the development) skills. The location of this research is done at the Tourism Village Purwodadi Malang, the sample is officers are on the process of education and learning the concept of tourism to rural communities, research analysis approach Patisipatory Rural Appraisal (PRA) and SWOT analysis menggenahi role of chaperone local tour guide (Local Guide, LG ). Cognitive, affective and psychomotor. The conclusion of this study were cognitively companion tour guide local (Local Guide, LG) has mastered the terrain, history and attractions and companion Guide menguasahi travel map geographical. Both affective companion tour guides have the power of a professional for assistance can print a local tour guide was very friendly. Psicomotoric third companion tour guide local (Local Guide, LG) has the power that the companion can create a tour guide become skilled in handling tourists.